Prognostication of Breast Cancer in Ghanaian Women Receiving Modified Radical Mastectomy: A Retrospective Histopathological Study at Korle-Bu Teaching Hospital, Accra, Ghana - Der, Edmund Muonir; Gyasi, Richard Kwasi; Wiredu, Edwin Kwame (Archives of Breast Cancer, 2018)
Background: Making prognosis and identifying the patients at higher risk of mortality are important issues in breast cancer (BC) treatment. The aim of this study was to stratify BC case receiving mastectomy into prognostic risk categories using the Nottingham Prognostic Index (NPI). Methods: This was a retrospective review from January 2002 to December 2014. Results: Approximately 35% of all BCs diagnosed in our institution had undergone mastectomy. The mean age was 51.9 years. The mean size of the primary breast tumor was 5.8 cm and showed significant association with the histologic grade (P = 0.001), nodal involvement (P < 0.001), positive tumor margins (P = 0.027), and the cancer stage (P < 0.001). Based on the NPI sores, 1.5% of the cases would have an excellent prognosis, 10.8% a good prognosis, 55.8% a moderate prognosis, and 31.9% a poor prognosis. Conclusion: The current study found that 87.7% of the women with breast had moderate to poor prognosis at the time of diagnosis. Patients are found to present late when the disease is advanced.